Ergebnisse (Ableitungsregeln)

    1. f'(x) = 100x99
    2. f'(x) = 21x6 + 55x4 - 24x - 7
    3. f'(x) = x/3 + 12x/5 - 3x/2 - 1/8
    4. f'(x) = -3/x4
    5. f'(x) = -6/x
    6. f'(x) = -2/x5
    7. f'(x) = -4/x7
    8. f'(x) = 2x + 2/3 + 4/x
    9. f'(x) = -9/x4 + 4/x - 1/(3x)
    10. f'(x) = -4/x5 + 18/x4 - 24/x + 8/x
    11. f'(x) = 1/(3·√x)
    12. f'(x) = 3√x/2
    13. f'(x) = 4/√x - 1/(2·4√x)
    14. f'(x) = 1/(6·√x) - 1/(2√x)
    1. y' = 8x + 4
    2. y' = 3x + 8x - 2
    3. y' = 12x + 27x - 10x - 15
    4. y' = 6x + 4x - 2
    5. y' = 24x
    6. y' = 10x4 - 4x + 42x - 28x + 29

    1. y' = 5/(x + 4)
    2. y' = -13/(3x - 5)
    3. y' = (-4x + 4)/(x+2)
    4. y' = (5x - 8x + 20)/(x - 4)
    5. y' = (12x + 20x - 21)/(6x + 5)
    6. y' = (x4 + 6x + 2x + 3)/(x + 3x)

    1. y' = 1 - 3/x
    2. y' = 1/3 - 3/x
    3. y' = 3
    4. y' = 1/4 + 2/x + 1/x
    5. y' = -4/x + 15/x4
    6. y' = -1/(4x) - 2/x4

    1. f'(x) = 10(2x + 3)4
    2. f'(x) = 6x(x - 9)
    3. f'(x) = -2x/(x + 3)
    4. f'(x) = -20/(10x - 3)
    5. f'(x) = 3/√(6x - 1)
    6. f'(x) = x/√(x - 4)

    1. f'(x) = (1 + x)·ex
    2. f'(x) = (2x + x)·ex
    3. f'(x) = (3x + 1)·ex
    4. f'(x) = (x - 1)·ex/x
    5. f'(x) = (2x - x)/ex
    6. f'(x) = 3e3x
    7. f'(x) = 0,1e0,1x+3
    8. f'(x) = 2x·ex

    1. f'(x) = ln x + 1
    2. f'(x) = (1 - ln x)/x
    3. f'(x) = 3·(ln x)/x
    4. f'(x) = 3/x
    5. f'(x) = 2/(2x - 5)
    6. f'(x) = 2x/(x + 1)

    1. f'(x) = cos x - sin x
    2. f'(x) = 1/cos x
    3. f'(x) = 3·cos(3x)
    4. f'(x) = 6·cos(2x + π)
    5. f'(x) = -2x·sin(x)
    6. f'(x) = 0

Zum Inhaltsverzeichnis